Star wars. Obi-Wan's foe : revenge of the Sith - Mason, Jane B.; Stephens, Sarah; Edwards, Tommy Lee (New York : Random House, 2005)
In the midst of the Clone wars, the Jedi Obi-Wan Kenobi is sent on a special mission which brings him face-to-face with General Grevious, the part-alien, part-robot commander of the droid armies.
"Lucas books."
4.8
3-6
Keywords: Kenobi, Obi-Wan (Fictitious character) -- Juvenile fiction; Good and evil -- Juvenile fiction; Space warfare -- Juvenile fiction; Kenobi, Obi-Wan (Fictitious character) -- Fiction; Good and evil -- Fiction; Space warfare -- Fiction; Science fiction; Kenobi, Obi-Wan (Fictional character) -- Fiction; Good and evil -- Fiction; Space warfare -- Fiction; Science fiction; Movie novels; Star Wars fiction; Science fiction; Movie novels